Use of ruminal fluid in drinking water of broilers raised in high altitude conditions - Castro Bedriñana, Jorge Isaac (2018)
The study was carried out in a farm located in the central highlands of Peru, at 3270 m above the sea level, to determine the effect of the use of three ruminal fluid levels in the drinking water of broilers. Two hundred Cobb chickens were used from the first day of age. The chicks were distributed in four groups of 50, in equal proportions of males and females. The treatments were: T1: drinking water alone (control); T2: 87.5% drinking water + 12.5% ruminal fluid; T3: 75% drinking water + 25% ruminal fluid; T4: 62.5% drinking water + 37.5% ruminal fluid. The chicks were fed with a starter diet for three weeks. The inclusion of ruminal fluid in drinking water improved weight gain and feed conversion (p<0.01). The use of 37.5% ruminal fluid in drinking water allowed a 19.4% increase in weight gain and a 15.5% increase in feed conversion.